101 great philosophers. - Pirie, Madsen, 1940- 4 0 16; 5 (London : Continuum, 2009)
A concise guide to the lives, thoughts, and contributions of 101 key philosophers from throughout history.
Includes index.
Keywords: 2 -- 0; 6; History.;History. -- Philosophy;Philosophers.;Philosophy;Philosophers.; 20; 2